Moral injury as an inclusive mental health framework for addressing climate change distress and promoting justice-oriented care. Issue 3 (March 2023) - Henritze, Evan; Goldman, Sonora; Simon, Sarah; Brown, Adam D
Summary: The unequal exposure to clinical conditions and other psychological responses associated with climate change and ecological degradation is due to resource access, geographical location, and other systemic factors. Ecological distress is further determined by values, beliefs, identity presentations, and group affiliations. Current models, such as climate anxiety, have made helpful distinctions between impairment and cognitive–emotional processes but obscure underlying ethical dilemmas and fundamental inequalities, restricting our understanding of accountability and the distress emerging from intergroup dynamics. In this Viewpoint, we argue that the concept of moral injury is essential because it foregrounds social position and ethics. It identifies spectrums of both agency and responsibility (guilt, shame, and anger) and powerlessness (depression, grief, and betrayal). The moral injury framework thus goes beyond an acontextual definition of wellbeing to identify how differential access to political power influences the diversity of psychological responses and conditions related to climate change and ecological degradation. A moral injury lens supports clinicians and policy makers to transform despair and stasis into care and action by delineating both the psychological and structural elements that determine the possibilities (and limits) of individual and community agency.